Strategi Pengembangan Koperasi Melalui Transformasi Digital - Intan Setyaningsih; Hidup Marsudi (JURNAL ILMIAH EDUNOMIKA, 2024)
The aim of this research is to determine the cooperative development strategy steps in carrying out digital transformation and the results obtained by cooperatives in developing digital transformation. Researchers will use a qualitative descriptive approach that studies existing problems and applicable work procedures. Qualitative research type. The research results obtained are that the digitalization of cooperatives offers various potential benefits that can increase efficiency, effectiveness and transparency, however, to realize this fundamental change, cooperatives must be ready to adapt and develop their technological capabilities and change organizational culture to be in line with the digital era. The digitalization of cooperatives brings many benefits to employees, from increasing efficiency and productivity to increasing welfare and career development, this not only benefits individual employees, but also supports the performance and growth of the cooperative as a whole. Keywords : Cooperatives, Digitalization, Management